(untitled) (Journal of Family Sciences, 2019)
Social support and marital adjustment play an important role in the realization of good marital quality. The purpose of this study is to analyze the characteristics of students and families, social support, marital adjustment along with the relationship and its effect on the marriage quality of married students. Examples of this study are 30 female students from various public and private universities in Bogor city taken with convenience sampling technique. The determination of research location was chosen purposively. Data collection was obtained from the interview using the questionnaire. Data were analyzed descriptively and inferential. The results showed that social support had a significant positive relationship with marital adjustment, while marital adjustment was positively correlated with marital quality. Social support and marital adjustment affect the quality of marriage.